2014
DOI: 10.1136/bcr-2014-203725
|View full text |Cite
|
Sign up to set email alerts
|

Acute three-vessel cervical arterial occlusion due to spontaneous quadruple cervical artery dissection

Abstract: Cervical artery dissection (CAD) is one of the most frequent causes (14.5%) of stroke in young adults. Cases with involvement of more than two arteries are rare. Arnold et al described 11 cases (1.5%) with triple CAD of a reported 740 patients and just a single (0.1%) quadruple case in the same population. Simultaneous dissection of the four principal vessels is extremely rare. According to Papagiannaki et al, the incidence of simultaneous three or four CADs is 1-3/million in the general population. To the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The embryological origin of the internal carotid artery is the same of the ascending aorta while the vertebral artery has the same embryological origin of the thoracic aorta; therefore, prospective studies might indicate more specific strategies for prevention and management of these two seemingly separate groups of dissection in cervical arteries [15]. Interestingly, Aronov et al, reported spontaneous quadruple cervical artery dissection, that is an exceeding rare condition with estimated incidence of 1 to 3 people per million of population [16]. Different of the present case, Yeh et al described traumatic VAD and Wallemberg syndrome ten hours after a minor motorcycle accident [12].…”
Section: Discussionmentioning
confidence: 99%
“…The embryological origin of the internal carotid artery is the same of the ascending aorta while the vertebral artery has the same embryological origin of the thoracic aorta; therefore, prospective studies might indicate more specific strategies for prevention and management of these two seemingly separate groups of dissection in cervical arteries [15]. Interestingly, Aronov et al, reported spontaneous quadruple cervical artery dissection, that is an exceeding rare condition with estimated incidence of 1 to 3 people per million of population [16]. Different of the present case, Yeh et al described traumatic VAD and Wallemberg syndrome ten hours after a minor motorcycle accident [12].…”
Section: Discussionmentioning
confidence: 99%
“…6 In most patients with multiple CADs, complete recanalization occurs in 78% of the dissected vessels and therefore medical treatment is sufficient. 7 Though our patient recovered from cerebral ischemia clinically, false lumen remained in both sides and recanalization was delayed indefinitely. Endovascular treatment would be reasonable in case of expanding pseudoaneurysm in our patient.…”
Section: What Is the Next Step In Management?mentioning
confidence: 99%
“…4 There are reports in the literature documenting the use of stents for reconstruction of occlusions secondary to vertebral artery dissections. [5][6][7][8][9][10][11][12][13][14] We present the case of a 27-year-old woman who presented after a syncopal event with headaches, ptosis, diplopia, and ataxia. Computed tomography angiogram demonstrated left vertebral artery dissection, near occlusion of the basilar artery, and a hypoplastic right vertebral artery.…”
mentioning
confidence: 99%